Patuntung: The Encounter of Local Culture and Islamic Sharia in the Ammatoa Kajang Community - Zainuddin; Jusalim Sammak; Salle (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2023)
The purpose of this research is to explore Patuntung belief among Ammatoa Kajang community and analyze the encounter between the belief and Islamic teaching. It relies on both primary and secondary data. Primary data was obtained through in-depth interviews and on-site observation. We interviewed ten key informants: four traditional leaders, three religious’ leaders, and three community leaders, while the observation was during July-September 2022. The secondary data was from literature exploration. The results of this study show that the Patuntung is the traditional belief of Ammatoa Kajang Community which has been still preserved today with its whole distinctive and unique features. Additionally, there also occurred encounter between Patuntung and Islamic belief as clear in the internalization of five Islamic pillars in Patuntung teachings. Quite different from those five which accentuate physical behaviors, Patuntung teaching stresses more on heartily intention and this makes the physical differences between the two inevitable.